External Influences on Southern African Transformations: ‘1989’ in Perspective - Saunders, Chris (Comparativ, 2019)
The changes in Southern Africa that began during the 1980s were due to a specific interaction of internal and external factors. However, this interplay must be placed in a historical perspective, because it goes back to the early 1960s, when decolonisation took hold of large parts of the continent, but also encountered coordinated resistance of the hitherto ruling powers in southern Africa, which led to a long social and military conflict that, like the Cold War in general, first weakened and then came to an end. The external shock of the revolutions in Eastern Europe brought the revolution in Africa, which had begun in 1960, to a successful end. The direct effect could be seen in South Africa, where the de Klerk government abandoned its fear of a Soviet-backed Communist takeover, while the ANC opened up to the prospect of a mixed and globally networked economy. The other states of southern Africa followed the general trend towards liberal democratic constitutions and elections to a very different degree, and the regional integration process initiated with the founding of SADC remains fragile. Nevertheless, in the end it can be concluded that the upheaval of 1989 was far more significant for the region than the subsequent caesura of 9/11 or the financial crisis of 2008–2010.